HEAVENLY TEARS EARTHLY LOSS: DIFFERENT WAYS OF COPING WITH LIFE LOSS IN TEARS IN HEAVEN, CIRCUS, AND SINCE I LOST YOU - Akun Akun (Soegijapranata Catholic University, 2014)
This is a qualitative study of three pop songs rooted from the same tragic event of Eric Clapton?s son Conor who fell from the 53rd floor of his spouse?s New York apartment in March 1991. Two songs are from Clapton himself i.e. Tears in Heaven and Circus and one song from his friend Phil Collins entitled Since I Lost You. The goal of this study is to elaborate the attitude of the author through the study of formal aspects of the song such as rhyme, rhythm, tone and picth and also the metaphorical expressions in their wording. This is a library research of the three songs using a comparative technique of elaboration. The study concludes that Phil Collins as a friend who is not directly involved in the tragedy shows his sympathy through a negative and hopeless way of seeing the tragedy. He focuses more on the tragedy directly rather than the impact, psychologial process and lessons learned afterward. Eric Clapton, on the other hand, as the one who directly suffers the impact of the tragedy sees the tragic event from a more positive angle. He tries to somehow show his grief but does not want to be drifted away in this sorrow. He focuses more on the process after the tragedyby remembering the sweet moment before the tragedy (in Circus) and imagine the same sweet thing after the tragedy (in Tears in Heaven) by setting an emotional spin around the good memory and nice after life state of the child with sweet hopes and strengthening consolation